Biology Reimagined: A test of Culturo-Techno-Contextual Approach (CTCA) in Boosting Students’ Achievement - M. Ige, Adeleke; Owolabi, Tunde; Onowugbeda, Franklin U.; Mustapha, Abiodun Gafar; Ogundowole, Ayodeji; Gbeleyi, Olasunkanmi A.; Olayanju, Mary; Armah, Micheal (FKIP - Universitas Riau, 2025)
The prerequisite for learning science lies in students' ability to adapt to new stimuli in learning environments. This ability is often reflected in their readiness to apply newly acquired knowledge in different contexts. This study investigated a culturally-influenced pedagogy infused with technological and contextual features to improve biology learning. A total of 138 Senior Secondary II students participated, comprising 75 students (45 males, 30 females) in the CTCA group and 63 students (30 males, 33 females) in the lecture group, with an average age of 15 years. An explanatory sequential mixed-method design was used. Quantitative data were collected using the Plant Nutrition Achievement Test (PNAT), which had a reliability coefficient of 0.83, while qualitative data were obtained through the Biology Students Interview Protocol in Biology (SIPB). Descriptive statistics (mean, standard deviation, and thematic analysis) and ANCOVA at a 0.05 significance level were used for data analysis. The findings showed that CTCA students significantly outperformed the lecture group [F (1,134) = 1655.16, p < .05]. Students also expressed positive attitudes toward CTCA. The study concludes that CTCA enhances students’ achievement in plant nutrition and recommends its adoption by biology teachers to engage students effectively.